Trichinella spiralis Excretory–Secretory Products Induce Tolerogenic Properties in Human Dendritic Cells via Toll-Like Receptors 2 and 4 - Ilic, Nataša; Gruden-Movsesijan, Alisa; Cvetkovic, Jelena; Tomic, Sergej; Vucevic, Dragana Bozidar; Aranzamendi, Carmen; Colic, Miodrag; Pinelli, Elena; Sofronic-Milosavljevic, Ljiljana (Frontiers in Immunology, 2018)
Trichinella spiralis, as well as its muscle larvae excretory–secretory products (ES L1), given either alone or via dendritic cells (DCs), induce a tolerogenic immune microenvironment in inbred rodents and successfully ameliorate experimental autoimmune encephalomyelitis. ES L1 directs the immunological balance away from T helper (Th)1, toward Th2 and regulatory responses by modulating DCs phenotype. The ultimate goal of our work is to find out if it is possible to translate knowledge obtained in animal model to humans and to generate human tolerogenic DCs suitable for therapy of autoimmune diseases through stimulation with ES L1. Here, the impact of ES L1 on the activation of human monocyte-derived DCs is explored for the first time. Under the influence of ES L1, DCs acquired tolerogenic (semi-matured) phenotype, characterized by low expression of HLA-DR, CD83, and CD86 as well as moderate expression of CD40, along with the unchanged production of interleukin (IL)-12 and elevated production of IL-10 and transforming growth factor (TGF)-β, compared to controls. The interaction with DCs involved toll-like receptors (TLR) 2 and 4, and this interaction was mainly responsible for the phenotypic and functional properties of ES L1-treated DCs. Importantly, ES L1 potentiated Th2 polarizing capacity of DCs, and impaired their allo-stimulatory and Th1/Th17 polarizing properties. Moreover, ES L1-treated DCs promoted the expansion of IL-10- and TGF-β- producing CD4+CD25hiFoxp3hi T cells in indolamine 2, 3 dioxygenase (IDO)-1-dependent manner and increased the suppressive potential of the primed T cell population. ES L1-treated DCs retained the tolerogenic properties, even after the challenge with different pro-inflammatory stimuli, including those acting via TLR3 and, especially TLR4. These results suggest that the induction of tolerogenic properties of DCs through stimulation with ES L1 could represent an innovative approach for the preparation of tolerogenic DC for treatment of inflammatory and autoimmune disorders.